2023
DOI: 10.1002/smll.202207260
|View full text |Cite
|
Sign up to set email alerts
|

Core/Shell ZnO/ZnS Nanoparticle Electron Transport Layers Enable Efficient All‐Solution‐Processed Perovskite Light‐Emitting Diodes

Abstract: Solution‐processed perovskite‐based light‐emitting diodes (PeLEDs) are promising candidates for low‐cost, large‐area displays, while severe deterioration of the perovskite light‐emitting layer occurs during deposition of electron transport layers from solution in an issue. Herein, core/shell ZnO/ZnS nanoparticles as a solution‐processed electron transport layer in PeLED based on quasi‐2D PEA2Csn−1PbnBr3n+1 (PEA = phenylethylammonium) perovskite are employed. The deposition of ZnS shell mitigates trap states on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…5a). 80 The ZnS shell can effectively suppress trap emission and interface non-radiation recombination of the ZnO core, at the same time, more favorable band alignment significantly improves the injection capability of electrons from the ETL to the perovskite layer (Fig. 5b and c).…”
Section: Ldnms Application In Charge-transport Modulationmentioning
confidence: 97%
“…5a). 80 The ZnS shell can effectively suppress trap emission and interface non-radiation recombination of the ZnO core, at the same time, more favorable band alignment significantly improves the injection capability of electrons from the ETL to the perovskite layer (Fig. 5b and c).…”
Section: Ldnms Application In Charge-transport Modulationmentioning
confidence: 97%
“…This indicates a significant improvement in device performance by reducing interface defects. [37] Extensive research has illuminated the significant influence of electron density and nucleophilicity, which can serve as a passivating mechanism for surface defects. [38] Wang et al reported on the molecular design of an ETL material with a more nucleophilic core group to enhance its electron-donating capability ultimately leading to the passivation of surface defects in the perovskite emissive layer at the interfacial region.…”
Section: Electron Transport Layermentioning
confidence: 99%
“…Additionally, the adsorption energy becomes more Reproduced with permission. [37] © 2023 WILEY-VCH GmbH negative, indicating enhanced interfacial electron transfer between the perovskite layer and the ETL through the incorporation of this highly nucleophilic material. Since these vacancy defects contribute significantly to trap-assisted nonradiative recombination and carrier accumulation, the theoretically designed passivation-capable ETL material demonstrated enhanced perovskite crystal quality by reducing Pb 2 + vacancies and surface defects.…”
Section: Electron Transport Layermentioning
confidence: 99%
“…In inverted structure PNC-LEDs, PEI interlayer reduces the workfunction of underlying ZnO layer, and ZnCl 2 interlayer in the middle of PNC layers slows down the transport of charge carriers, both of which were used to increase the electron injection and improve charge balance in devices. Furthermore, all-inorganic electron transport layer such as ZnO/ZnS core/shell nanocrystals were used to increase the electron injection and improve charge balance in devices …”
Section: Device Engineeringmentioning
confidence: 99%